Wide-ranging and Violent Volcanic History of a Quiet Transborder Area: Volcanic Geoheritage of the Novohrad–Nógrád UNESCO Global Geopark - Szabolcs Harangi; Imre Szarvas; Réka Lukács (Geoconservation Research)
The Novohrad–Nógrád UNESCO Global Geopark is the first cross-border geopark located between Slovakia and Hungary, Eastern–Central Europe. “Ancient world without borders” – its motto reflects both the remarkable geodiversity and the strong link between people living on either side of the state border. In this relatively small area, almost all types of eruption products can be found from basaltic through andesitic to rhyolitic, reflecting the wide-ranging volcanism of the Pannonian Basin over the last 20 million years, which were the largest eruptions in Europe at the time. The Ipolytarnóc Site, the gateway of the geopark and possessor of a European- Diploma for Protected Areas, documents when one of these devastating eruption events buried a subtropical-forested area with thick pyroclastic deposits and preserved vertebrate footprints. On the other hand, relatively young eruptions of basaltic magmas occurred in this area that give another specific atmosphere to the geopark. Columnar jointing with concave and convex curvilinear shapes shown both by basalts and andesites is another peculiar natural value. Due to the regional uplift and the associated erosion, most of the volcanic edifices were removed and the root zones of the volcanoes were revealed, giving a special character. The volcanic heritage meets specific cultural and historical heritage, which makes this geopark a particular tourist destination. There are four visitor centers and several nature trails with explanation panels showing concise summaries of the volcanological features in three languages (Hungarian, Slovakian and English). Among the rich indoor and outdoor activities, the annual Volcano Day program in Ipolytarnóc with an interactive volcano show attracts many people. This is an evolving geopark, where continuously renewing attractions serve the geoeducation and geotourism purposes in parallel with geoheritage conservation management.